Wnts and Hedgehogs: lipid-modified proteins and similarities in signaling mechanisms at the cell surface. - Nusse, R. (Development, 2003)
This review compares the signaling mechanisms of the Wnt and the Hedgehog proteins. Although Wnts and Hedgehogs are unrelated proteins, they are both modified by lipids, possibly through the action of enzymes that are related to each other. At the surface of target cells, the reception of Wnt and Hedgehog signals is regulated by several molecules, some of which, in particular the Frizzled and Smoothened receptors, are related to each other. Several other aspects of Wnt and Hedgehog transport and signaling are discussed, as well as the possible origin of these pathways.